Pengaruh Media Audiovisual terhadap Tingkat Pengetahuan dan Sikap Cuci Tangan Pakai Sabun (CTPS) yang Baik dan Benar di SD Yaspenhan Medan Marelan - Arifin, Arifin Shaleh Lubis; Nanda, Meutia; Ismah, Zata (LPPM Hang Tuah Pekanbaru, 2024)
SD Yaspenhan Medan Marelan is still not equipped for hand washing with soap (CTPS) activity facilities such as the absence of soap in the hand washing place and there is no health promotion media in the form of posters or leaflets around the school environment. Some students still do not understand the habit of washing hands with soap (CTPS), there is no implementation carried out in the Sd and it can also be said that knowledge and attitudes are still minimal regarding hand washing with soap (CTPS). This study aims to see the effect of audio-visual media on the knowledge and attitude of hand washing with soap that is good and right for students in grades III and IV. This research method uses Experimental Design with the